DOPS assessment: A study to evaluate the experience and opinions of trainees and assessors†. (June 2013) - Bindal, Natish; Goodyear, Helen; Bindal, Taruna; Wall, David
<x xml:space="preserve">Abstract</x> Background: Workplace based assessments (WBAs) have been part of UK training for the last 3 years. Carrying out procedures efficiently and safely is of paramount importance in anaesthesia. Aims: To explore opinions and experiences of Direct Observation of Procedural Skills (DOPS) assessments in a regional anaesthetic training programme. Methods: 19 and 20-item questionnaires were distributed to trainees and consultants respectively. Results: Questionnaire response rate was 76% (90/119) for trainees and 65% (129/199) for consultants. 43% of consultants and 33% of trainees were not trained in DOPS use. Assessments were usually not planned. 50% were ad hoc and the remainder mainly retrospective. Time spent on assessment was short with DOPS and feedback achieved in ≤15 minutes in the majority of cases with lack of suggestions for further improvement. Both trainees and consultants felt that DOPS was not a helpful learning tool (p = 0.001) or a reflection of trainee competency. Conclusions: DOPS assessments are currently not valued as an educational tool. Training is essential in use of this WBA tool which needs to be planned and sufficient time allocated so as to address current negative attitudes.